KETIDAKPASTIAN LINGKUNGAN SEBAGAI VARIABEL PEMODERASI HUBUNGAN ANTARA PENYUSUNAN ANGGARAN PARTISIPATIF DENGAN KINERJA MANAJERIAL (STUDY PADA UNIVERSITAS SLAMET RIYADI SURAKARTA - ., Edi Wibowo (Jurnal Akuntansi dan Sistem Teknologi Informasi, 2006)
ABSTRACT The main objective of this study is to investigate the relationship between budgetary participation and managerial performance. This study is also  intended to provide evidence on the influence of the environment uncertainty towards relationship between budgetary participation and managerial performance. Uncertainty of environment is as moderating variable that affecting the relationship between budgetary participation and managerial performance. The sample of this study is employee of the personals or employees staff of the Slamet Riyadi University Surakarta have structural position that consists of 46 persons used the Purposive Sampling method. The instrument used questionnaire to elaborate from worker opinion about budgetary participation, managerial performance, and  the environment uncertainty. The first hypothesis used correlation Pearson analysis and the second hypothesis used multiple linear regression. The result of first hypothesis with correlation Pearson analysis shows that there is a positive and significant  relationship between budgetary participation towards managerial performance with level correlation is strong, so  the result of seconds hypothesis with multiple linear regression shows the environment uncertainty to influence towards level of relationship between with managerial performance. Keywords: Budgetary participation, The environment uncertainty, managerial performance